Subsurface banding increases ammonia emissions under rainfed cotton in Florida sandy soils - Singh, Kulpreet; Dar, Eajaz A.; Singh, Satinderpal; Shah, Akash; Sharma, Lakesh; Singh, Hardeep (Frontiers in Agronomy, 2025)
Ammonia (NH3) volatilization is a significant pathway for nitrogen (N) loss. The acidic, sandy soils of Florida offer ideal conditions for NH3 losses in rainfed cotton production systems. To assess NH3 losses under various N placement methods and rates, the experiment was conducted in 2023 and 2024 using a randomized complete block design with four replications. The study employed two placement methods: surface broadcasting and subsurface banding, and two N rates: 67.5 and 102 kg N/ha. Ammonia emissions were measured using open-chamber traps, with sampling conducted multiple times per week. Daily NH3 emissions (g/ha/day) were averaged over each week, and cumulative emissions (g/ha) were calculated by summing weekly averages across the sampling period. These cumulative values were then used to estimate total NH3-N losses, expressed as a percentage of the total N applied. Sampling weeks were referenced as WAF (weeks after fertilization) to standardize timing across both years. Results indicated that both daily and cumulative NH3; emissions were significantly higher with subsurface banding compared to surface broadcasting, leading to greater N-NH3; losses under banding. In addition, neither placement method nor N rate significantly influenced cotton lint yield. These findings suggest that, under the conditions of this study, subsurface banding increased NH3 volatilization losses in rainfed cotton grown on sandy soils in Florida.